2015
DOI: 10.3109/0886022x.2015.1009820
|View full text |Cite
|
Sign up to set email alerts
|

Use ofOphiocordyceps sinensis(syn.Cordyceps sinensis) combined with angiotensin-converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB) versus ACEI/ARB alone in the treatment of diabetic kidney disease: a meta-analysis

Abstract: . This meta-analysis suggested that use of O. sinensis combined with ACEI/ARB may have a more beneficial effect on the proteinuria, inflammatory, dyslipidemia status as compared to ACEI/ARB alone in DKD III-IV stage patients, while there is no evidence that O. sinensis could improve the hyperglycemia status. However, with regard to low-quality and significant heterogeneity of included trials, to further verify the current results from this meta-analysis, long-term and well-designed RCTs with high-quality study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…Certain hypotensive drugs and oral hypoglycemic drugs, such as ACEIs, angiotensin II receptor blockers, metformin and gliclazide, exert various pharmacological actions, with anti-inflammatory and antioxidative effects (12,16). However, studies indicate that inflammation and oxidative stress cannot be adequately controlled using these medications alone (17)(18)(19)(20)(21)(22)(23). Drugs possessing anti-inflammatory and antioxidative effects appear to be necessary for hypertensive patients with T2DM who are at high risk of vascular complications.…”
Section: Renoprotective Effects Of Berberine As Adjuvant Therapy For mentioning
confidence: 99%
“…Certain hypotensive drugs and oral hypoglycemic drugs, such as ACEIs, angiotensin II receptor blockers, metformin and gliclazide, exert various pharmacological actions, with anti-inflammatory and antioxidative effects (12,16). However, studies indicate that inflammation and oxidative stress cannot be adequately controlled using these medications alone (17)(18)(19)(20)(21)(22)(23). Drugs possessing anti-inflammatory and antioxidative effects appear to be necessary for hypertensive patients with T2DM who are at high risk of vascular complications.…”
Section: Renoprotective Effects Of Berberine As Adjuvant Therapy For mentioning
confidence: 99%
“…A polysaccharide obtained from the cultural mycelium of Cordycepssinensis showed potent hypoglycemic activity in genetic diabetic mice after intraperitoneal administration, and the plasma glucose level was quickly reduced in normal and streptozotocin-induced diabetic mice after intravenous administration [34][35]. The diabetic rats had significantly lower weight gain and higher blood glucose response in oral glucose tolerance test than the control rats; and these changes were significantly reduced by administrating the fruiting body of Cordyceps and these improvements suggested that fruiting body of Cordyceps has a potential to be the functional food for diabetes [36]. Another research revealed that isolated polysaccharide from C. sinensis, named CSP-1 produced a significant drop in blood glucose level in both STZ-induced diabetic rats and alloxan-induced diabetic mice [36].…”
Section: Cordyceps Sinensismentioning
confidence: 96%
“…A polysaccharide obtained from the cultural mycelium of Cordycepssinensis showed potent hypoglycemic activity in genetic diabetic mice after intraperitoneal administration, and the plasma glucose level was quickly reduced in normal and streptozotocin-induced diabetic mice after intravenous administration [34][35]. The diabetic rats had significantly lower weight gain and higher blood glucose response in oral glucose tolerance test than the control rats; and these changes were significantly reduced by administrating the fruiting body of Cordyceps and these improvements suggested that fruiting body of Cordyceps has a potential to be the functional food for diabetes [36]. Another research revealed that isolated polysaccharide from C. sinensis, named CSP-1 produced a significant drop in blood glucose level in both STZ-induced diabetic rats and alloxan-induced diabetic mice [36].…”
Section: Cordyceps Sinensismentioning
confidence: 99%